AB0022 Family-based whole-exome sequencing reveals the genetic basis of relapsing polychondritis. (12th June 2018) - Lin, Z.; Gui, L.; Qi, J.; Guo, X.; Lv, Q.; Zhang, Y.; Fang, L.; Zhang, X.; Gu, J.
Abstract : Background: Relapsing polychondritis (RP) is a rare systemic disease, characterised by recurrent episodes of inflammation of cartilaginous tissues and other proteoglycan rich structures involving the cartilage of the ears, nose, larynx, tracheobronchial tree and cardiovascular system. 1 2 The susceptibility to RP has been reported to be significantly related to genetic factors. 3 4 However, family occurrence has yet to be reported and the responsible molecular genetic determinants hasn't been clearly elucidated. Objectives: The purpose was to detect the susceptibility genes of RP through whole-exome sequencing (WES) in a Chinese family and deepen our understanding of the pathogenesis of RP. Methods: A 32 year-old Chinese female proband with RP and her family in which only her mother was RP patient were recruited in the current study. The genomic DNA of 6 human subjects was extracted from the peripheral blood monocyte cells (PBMCs) and then identified gene allele mutations using WES. Candidate variants with low frequency (<0.1%) in general population and predicted deleterious on gene function were identified. Sanger sequencing was then used to validate the analysis results of WES and further validated the gene variants in 12 human subjects. Results: 38 genes mutated were confirmed by WES among RP patients. Of them, 10 gene mutated were validated by Sanger sequencing, including Collagen Type XXII Alpha 1 Chain (COL22A1) rs200464636, folliculin (FLCN) NM_144606: c.G838A: p.E280K, glycosylphosphatidylinositol anchor attachment 1 (GPAA1) rs201424010, DNA ligase 3 (LIG3) rs761808558, RecQ like helicase 4 (RECQL4) rs757703895, ring finger protein 207 (RNF207) NM_207396: c.T425C:p.I142T, coiled-coil domain containing 61 (CCDC61) rs777816675, Purkinje cell protein 2 (PCP2) rs144974437, tubulin alpha 3e (TUBA3E) rs749780020 and myosin heavy chain 15 (MYH15) NM_014981: c.G4462A: p.A1488T. Conclusions: This study confirms that coinheritance of multigene mutated may contribute to the susceptibility to RP. The candidate genes mutated we discovered are potential targets for in-depth functional studies. References: [1] McAdam LP, O'Hanlan MA, Bleustone R, Pearson CM. Relapsing polychondritis: prospective study of 23 patients and review of the literature. Medicine (Baltimore)1976;55:193–215. [2] Trentham DE, Le CH. Relapsing polychondritis. Ann Intern Med1998;129:114–122. [3] Lang B, Rothenfusser A, Lanchbury JS, Rauh G, Breedveld FC, Urlacher A, Albert ED, Peter HH, Melchers I. Susceptibility to relapsing polychondritis is associated with HLA-DR4.Arthritis Rheum1993;36(5):660–664. [4] Zeuner M, Straub RH, Rauh G, Albert ED, Scholmerich J, Lang B. Relapsing polychondritis: clinical and immunogenetic analysis of 62 patients. J Rheumatol1997;24(1):96–101. Acknowledgements: This study was supported by Guangdong Natural Science Funds for Distinguished Young Scholar (Grant No. 2014A030306039), High-level personnel of special support program for Technology Innovative Talents and the Top Young of Guangdong Province (Grant No.2015TQ01R516), Distinguished Young Scholar Candidates Programme for The Third Affiliated Hospital of Sun Yat-Sen University and Pearl River Nova Program of Guangzhou (Grant No. 201610010005). Disclosure of Interest: None declared